The Hands-on Model of the Internet: Engaging Diverse Groups of Visitors. (1st July 2014) - Shea, Michael
Abstract: Based on ethnographic field research at the Miraikan National Museum of Emerging Science and Innovation in Tokyo, this article uses the Hands-on Model of the Internet in the Future, Innovation, and Society section of the museum as a case study in the various issues related to effective public engagement in science museums. Museum exhibit design and implementation is critically assessed in terms of the role of educators and volunteers, the balance of educational and entertainment properties, and how exhibits and their accompanying explanatory material must cater to audiences of mixed age and scientific experience. It will be argued that the hands-on model has endured over the past ten years due to its successful negotiation of these elements.